2008
DOI: 10.1007/s12010-008-8174-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autolysis in Aspergillus nidulans

Abstract: In terms of cell physiology, autolysis is the centerpiece of carbon-starving fungal cultures. In the filamentous fungus model organism Aspergillus nidulans, the last step of carbon-starvation-triggered autolysis was the degradation of the cell wall of empty hyphae, and this process was independent of concomitantly progressing cell death at the level of regulation. Autolysis-related proteinase and chitinase activities were induced via FluG signaling, which initiates sporulation and inhibits vegetative growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(119 citation statements)
references
References 58 publications
3
116
0
Order By: Relevance
“…1). Addition of 4 g/l yeast extract to the medium hindered both DCM declination and extracellular chitinase production (extracellular chitinase activity factored with DCM), which is a good marker of autolytic cell wall degradation [4], was also higher in minimal medium than those found in yeast-extract-supplemented nutrient-rich medium (Fig. 1).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…1). Addition of 4 g/l yeast extract to the medium hindered both DCM declination and extracellular chitinase production (extracellular chitinase activity factored with DCM), which is a good marker of autolytic cell wall degradation [4], was also higher in minimal medium than those found in yeast-extract-supplemented nutrient-rich medium (Fig. 1).…”
mentioning
confidence: 98%
“…In previous experiments, we studied the glucose-mediated repression of autolysis in A. nidulans. We found that glucose repressed the autolytic cell wall degradation via the carbon catabolite repressor CreA as well as independently of CreA, via repressing the conidiogenesis regulatory gene brlA and activating the heterotrimeric G protein FadA-dependent signalling [4, 8].Here, we studied the effect of yeast extract on the autolysis of A. nidulans. We demonstrated that the bZip-type transcription factor MeaB, an activator of nmrA expression and a co-repressor of areA expression [9], was involved in the yeast-extract-mediated repression of autolytic cell wall degradation.…”
mentioning
confidence: 99%
See 3 more Smart Citations